Trig. Identities & Calculus Standard Results Flashcards
sin(A+B)=
sinAcosB + cosAsinB
sin(A-B)=
sinAcosB - cosAsinB
cos(A+B)=
cosAcosB - sinAsinB
cos(A-B)=
cosAcosB + sinAsinB
tan(A+B)=
tanA + tanB / 1 - tanAtanB
tan(A-B)=
tanA - tanB / 1 + tanAtanB
sin2A=
2sinAcosA
cos2A=
cos^2A - sin^2A
2cos^2A - 1
1-2sin^2A
tan2A=
2tanA / 1 - tan^2A
sin^2x + cos^2x =
1
1 + tan^2x =
sec^2x
1 + cot^2x =
cosec^2x
secx =
1/cosx
cosecx =
1/sinx
cotx =
1/tanx
tanx =
sinx/cosx
cotx =
cosx/sinx
f(x) = sinx
f’(x) =
cosx
f(x) = cosx
f’(x) =
-sinx
f(x) = a^x
f’(x) =
a^x . ln(a)
f(x) = e^x
f’(x) =
e^x
f(x) = ln(f(x))
f’(x) =
f’(x) / f(x)
f(x) = f(g(x))
f’(x) =
f’(g(x))g’(x)
chain rule
f(x) = f(x)g(x)
f’(x) =
f’(x)g(x) + f(x)g’(x)
u’v + uv’
product rule
f(x) = f(x)/g(x)
f’(x) =
f’(x)g(x) - f(x)g’(x) / (g(x))^2
u’v - uv’ / v^2
quotient rule
f(x) = tanx
f’(x) =
sec^2(x)
f(x) = secx
f’(x) =
sec(x)tan(x)
f(x) = cotx
f’(x) =
-cosec^2(x)
f(x) = cosecx
f’(x) =
-cosec(x)cot(x)